Workplace Exercise for Control of Occupational Neck/Shoulder Disorders a Review of Prospective Studies - Brian D. Lowe; Robert B. Dick (SAGE Publishing, 2014)
A review was conducted of prospective studies (1997-2014) examining the efficacy of exercise as a workplace intervention to control neck/shoulder pain, symptoms, and disability. The review identified 38 relevant studies - 20 were classified with positive effects, 13 with null effects, and 5 as inconclusive. Of the positive studies, 12 were consistent with Level I evidence, 3 with Level II evidence, and 5 with Level IV evidence. Specific resistance training (SRT) exercise appeared to be associated with more positive studies (eight Level I studies) than other exercise modalities such as general resistance training, general physical exercise, stretching, and movement awareness exercises. Studies of longer trial duration tended toward more null findings and lower program compliance. Evidence for a primary preventive effect of workplace exercise is minimal. The findings of this review suggest that workplace exercise can be effective as tertiary prevention and therapeutic relief of neck/shoulder symptoms, at least over the shorter term.